Pengaruh Kompetensi Guru Terhadap Mutu Pendidikan di SD Bunda Hati Kudus Jakarta - Meli Sova Br Saragih; Hotmaulina Sihotang (JPT : Jurnal Pendidikan Tematik, 2025)
Schools as formal educational institutions are required to continuously improve the quality of educational services provided to students. In this process of sustainability, teachers are the central actors. So, is there a relationship between teacher competence and the quality of education at the school level? This study uses a qualitative descriptive approach with a literature review. The results of the study indicate that teacher competence affects the quality of education in elementary schools. The results of this study are evidenced by an analysis of the influence of teacher competence on the quality of education at SD Bunda Hati Kudus Jakarta.